Resting state functional connectivity of networks associated with reward and habit in anorexia nervosa. Issue 2 (25th September 2018) - Haynos, Ann F.; Hall, Leah M. J.; Lavender, Jason M.; Peterson, Carol B.; Crow, Scott J.; Klimes‐Dougan, Bonnie; Cullen, Kathryn R.; Lim, Kelvin O.; Camchong, Jazmin
Abstract: Neurobiological disturbances associated with reward and/or habit learning are theorized to maintain symptoms of anorexia nervosa (AN). Although research has investigated responses in brain regions associated with reward and habit to disorder‐specific cues (e.g., food) and presumed rewards (e.g., money), little is known about the functional organization of the circuits underlying these constructs independent of stimulus. This study aimed to provide initial data on the synchrony of networks associated with reward and habit in AN by comparing resting‐state functional connectivity (RSFC) patterns between AN and healthy control (HC) participants in these circuits and delineating how these patterns relate to symptoms. Using theoretically selected seeds in the nucleus accumbens (NAcc), ventral caudate, and dorsal caudate, reflecting a continuum from reward‐ to habit‐ oriented regions, RSFC patterns were compared between AN restricting subtype ( n  = 19) and HC ( n  = 19) participants (cluster threshold: p  < .01). Exploratory correlations between RSFC z‐scores and Eating Disorder Examination (EDE) scores, BMI, and illness duration were conducted. The AN group demonstrated lower RSFC between the NAcc and superior frontal gyrus, between the ventral caudate and frontal and posterior regions, and between the dorsal caudate and frontal, temporal, and posterior regions. In the AN group, lower NAcc‐ superior frontal gyrus RSFC correlated with greater EDE Global scores ( r  = −.58, CI: −.83, −.13). These resting‐state synchrony disruptions of the ventral and dorsal frontostriatal circuits, considered in context of the broader literature, support the utility of further investigating possible reward and habit disturbances supporting symptoms in AN.